(untitled) (Singaporean Journal of Business Economics and Management, 2015)
Enterprise resource planning (ERP) systems have revolutionised the way organisations do business. It has integrated the different business functions into a single common database providing important information for top management to make effective business decisions. Although ERP systems can be extremely costly to implement and maintain the rewards that can be derived from the system are great and have benefited many organisations.